Encyclopedia of positive questions : volume 1: using appreciative inquiry to bring out the best in your organization. - Whitney, Diana, ....-; Cooperrider, David L., ....-; Trosten-Bloom, Amanda, ....- (Brunswick : Crown Custom, 2005)
Human systems and organizations move in the direction of what they study--is the premise and focus of this practical handbook. The book is composed of generic interview questions central to the Discovery phase of the Appreciative Inquiry process. Appreciative interview questions <javascript:void(0) > such as those discussed in this book seek to discover who and what the organization is, at its best